Tensile tests of composite coupons with prescribed porosity - Seah, Sin Wei. (2013)
The applications of carbon fibre reinforced polymers (CFRP) are gaining momentum in the aerospace and automotive industries. The great strength-to-weight ratio provided by CFRP had helped not only to reduce the weight, but also the costs through lower fuel consumption. Porosity, which is a common defect that can occur during the manufacturing process, affects the properties of CFRP greatly. Therefore, this project aims to determine how does varying porosity level affects the tensile properties of CFRP.